2021
DOI: 10.1007/s10803-021-05015-7
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Recognising Dynamic but not Static Emotional Body Movements in Autism Spectrum Disorder

Abstract: In this study, we investigated whether the difficulties in body motion (BM) perception may led to deficit in emotion recognition in Autism spectrum disorder (ASD). To this aim, individuals with high-functioning ASD were asked to recognise fearful, happy, and neutral BM depicted as static images or dynamic point-light and full-light displays. Results showed slower response times in participants with ASD only in recognising dynamic stimuli, but no group differences in accuracy. This suggests that i) a deficit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 91 publications
(145 reference statements)
0
10
0
Order By: Relevance
“…(ii) Autistic traits and body language reading. Mounting evidence points to alterations of both BM processing and affective body language reading in ASD ( Hubert et al, 2007 ; Freitag et al, 2008 ; Atkinson, 2009 ; Klin et al, 2009 ; Kaiser et al, 2010 ; Nackaerts et al, 2012 ; Pavlova, 2012 ; Centelles et al, 2013 ; Mazzoni et al, 2020 , 2021 ; Jack et al, 2021 ; Sotoodeh et al, 2021 ; for review, see Pavlova, 2012 ; Barton, 2021 ), though intact BM processing is also reported ( Murphy et al, 2009 ). Most important, the sensitivity to BM is inversely linked both to the severity of ASD ( Blake et al, 2003 ) and to autistic symptomatology as measured by the autistic diagnostic observation schedule (ADOS) in adolescents ( Koldewyn et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Autistic traits and body language reading. Mounting evidence points to alterations of both BM processing and affective body language reading in ASD ( Hubert et al, 2007 ; Freitag et al, 2008 ; Atkinson, 2009 ; Klin et al, 2009 ; Kaiser et al, 2010 ; Nackaerts et al, 2012 ; Pavlova, 2012 ; Centelles et al, 2013 ; Mazzoni et al, 2020 , 2021 ; Jack et al, 2021 ; Sotoodeh et al, 2021 ; for review, see Pavlova, 2012 ; Barton, 2021 ), though intact BM processing is also reported ( Murphy et al, 2009 ). Most important, the sensitivity to BM is inversely linked both to the severity of ASD ( Blake et al, 2003 ) and to autistic symptomatology as measured by the autistic diagnostic observation schedule (ADOS) in adolescents ( Koldewyn et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli were taken from Mazzoni et al (2022) and consisted of 12 pictures displaying the bodies of four actors (two females) enacting fearful, happy, and neutral postures with blurred faces on a black background. In all pictures, individuals performed meaningful actions so that both emotional and neutral images illustrated biological movements.…”
Section: Methodsmentioning
confidence: 99%
“… Twelve colored pictures were taken from Mazzoni et al (2022) database. Photos displayed the bodies of two actors and two actresses with blurred faces on a black background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the many well-established tools available for studying emotion recognition from faces, there has long been a relative paucity of tools to assess emotion recognition from body expressions. Over the last two decades, however, the interest in studying emotional body expressions has steadily increased, leading to the development of different emotional body datasets (examples using static stimuli: e.g., 19 , 20 , examples using dynamic stimuli: e.g., 21 24 ). Thoroughly validated tools that attempted to include both face and body expressions alongside each other remain scarce, however (e.g., the PONS test 25 or the Bochum Emotional Stimulus Set 26 ).…”
Section: Introductionmentioning
confidence: 99%